Obstacles of ending TB: What does health system think? - Soodabeh Hoveidamanesh; Behnaz Soleimani Tapehsari; Zahra Rampisheh; Massomeh Goshtaei; Peyman Parchami; Salimeh Goharinezhad (Shahid Beheshti University of Medical Sciences, 2018)
Background: Despite the importance of Tuberculosis (TB) control program and elimination of disease as its target, only a few studies have been carried out to evaluate tuberculosis control in Iran. In the present study, we intended to ask the opinions from experts and managers of Iran University of Medical Sciences about the TB control program in Iran. Methods: A Qualitative study was carried out to determine experts' and managers' opinions about the national TB control program. Experts and stakeholders were listed for focus group discussions (FGD) and interviews using purposive sampling method. We interviewed all levels of staff involved in the tuberculosis control program (managers, physicians, and administrative and executive staffs). Three FGD sessions were held with 28 participants. The participants were excluded if they had less than six months of experience in TB program. FGD and interviews were manually coded and the themes and sub-themes were extracted. After analyzing the results, the final report was drafted. Results: The results were classified into four themes and 15 subthemes (6 in input, 3 in process, 2 in outputs, and 4 in outcome). There were positive points and problems in each part. To achieve the goal of End TB, we will need to review the process, incorporate with other sectors, apply new diagnostic methods, and participate with other stakeholders (internal and external). Conclusion: Because of the effects of socio-economic factors on tuberculosis, considering the current implementation of the program; it is not possible to eliminate tuberculosis.